Dialogue of Cultures and Ideas in Ivan Rukavishnikov’s Prose - Szymonik, Danuta (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The article deals with the problems of dialogue of cultures and ideas in prose pieces by Ivan Rukavishnikov (1877–1930), a Russian poet of the Silver Age, writer, cultural activist and translator. Rukavishnikov’s works are characterized by ideological and aesthetic tendencies typical of the Russian culture at the turn of the 20th century. In contemporary research parallels have been drawn between the prose of Rukavishnikov and that of Fyodor Dostoyevski, Fyodor Sologub, Valery Bryusov, Andrei Bely, Mikhail Albov and Vladimir Nabokov, among others. Rukavishnikov’s early verse is marked by the motifs of death, illness and loneliness. The majority of Rukavishnikov’s poems describe the poet’s feelings and emotions through images of weakness, disappointment, sorrow, suffering, fatigue and weariness, typical of the ‘lost generation’ poets. The same motifs are characteristic of his prose. The autobiographical persona from the lyrical poetry has a correspondent in the novel The Damned Family – the autobiographical figure of Viktor Makarovich, an artist and a typical individualist, focused on his personal feelings. As the author’s porte parole, Makarovich discusses art topics with other characters in the novel, and sometimes with himself. These artistic and intellectual discussions reflect the essence of actual Silver Age literary polemics. In the article the author also analyzes Rukavishnikov’s interest in Hindu ideas and culture, expressing the human longing for truth and perfection (manifest in the second part of the collection The Close and the Distant). By referring to the ancient philosophy the writer raises universal and timeless questions. These questions do not belong only to the spiritual and physical world of Rukavishnikov as a representative of the Russian Silver Age, but remain topical nowadays as well.